People at a y-Walk party - Unknown:::Creator::::::::::::
Photograph shows men and women sitting at an outdoor table with drinks on it. They are probaby at D.B. Cooper's for a y-Walk party and are wearing y-Walk stickers on their clothes. The man in the middle is holding up both his hands with his fingers making the peace sign. The man to the right of him is holding his right hand up with his fingers making the hang loose sign. The men and two of the woman appear to be African American, the third woman may be a Mexican American.